Răspunsuri

2014-11-18T19:25:23+02:00
A (6+(5+(3·x-64):7):7):7=1
(6+(5+(3·x-64):7):7)=7
(6+(5+(3·x-64):7)=7*7
(6+(5+(3·x-64):7)=49
(6+(5+(3·x-64)=49*7
(6+(5+(3·x-64)=343
(5+(3·x-64)=343-6
(5+(3·x-64)=337
3·x-64=337-5
3·x-64=332
3·x=332+64
3·x=396
x=396:3
x=132

B (5+(4+(4·x-56):6):6):6=1

(5+(4+(4·x-56):6):6)=6

(5+(4+(4·x-56):6=6*6

(5+(4+(4·x-56):6=36

(5+(4+(4·x-56)=36*6

(5+(4+(4·x-56)=216

(4+(4·x-56)=216-5

(4+(4·x-56)=211

4·x-56=211-4

4·x-56=207

4·x=207+56

4·x=263
 x=263/4




















2014-11-18T19:53:26+02:00